An Exegetical and Theological Analysis of Ephesians 4:1-16 and Its Relevance for the Church of Pentecost, Ghana - Allotey, F.A. (University of Ghana, 2019)
Paul in Eph. 4:1-16 exhorts the believers to maintain the unity that has been initiated by the Holy Spirit through the redemptive and reconciliatory work of Christ. He identifies the essence of the unity to be rooted in the existence of a sevenfold uniform creedal ele-ments shared by the believers. Each believer has received a gift according to the measure of Christ’s grace. Christ has given apostles, prophets, evangelists, pastors and teachers as leadership gifts to the church, with the core duty of equipping the other believers to attain the Christian community’s goals of unity and maturity. The relationship that exists among these leadership gifts to a large extent affects the realisation of the community’s goals of unity and maturation. The Church of Pentecost (CoP), an international classical Pentecostal denomination with headquarters in Accra, Ghana employs a complementary and a hierarchical relationship among these leadership gifts in its polity. The research examines the biblical basis of such a working relationship chosen by the CoP and how it affects its pursuit of communi-ty unity and maturation. The three-step Communicative Approach to biblical study proposed by George Ossom-Batsa is used as the theoretical framework. The exegesis of the text was carried out using the six-step Rhetorical Criticism approach proposed by George Kennedy. Data for the exegesis of the culture of the CoP were collected through personal observations, inter-views and focus group discussions. The Sefwi Boako English Assembly of the CoP is chosen for the focus group discussion. An intercultural engagement between the text and the reality revealed that there is no strong biblical basis for the hierarchical working relationship among the leadership gifts in the CoP. Though the working relationship ensures orderliness and promotes optimal performance by ministers, it also breeds manipulations, envy, unhealthy strife for posi-tions and reduces the divine callings into job positions and titles. Finally, the research recommends that institutional authority should be dissociated from a person’s divine calling. It also offers suggestions for further academic researches on the leadership gifts.
MPhil.
Keywords: Ephesians 4:1-16; Church of Pentecost; Ghana